Retinoids are not linked to risk of multiple sclerosis: A Danish nationwide cohort study. (30th September 2021) - Cortes‐Figueiredo, Filipe; Nielsen, Nete Munk; Stenager, Egon; Paul, Friedemann; Hallas, Jesper; Kristensen, Kasper Bruun
Abstract: Background and purpose: Multiple sclerosis (MS) is a chronic immune‐mediated disease of the central nervous system with an undetermined etiology. Retinoids may have immunomodulatory effects that favorably influence MS progression. We aimed to explore the yet unknown relationship between exposure to retinoids and the risk of acquiring MS. Methods: We performed a nationwide cohort study in the Danish population in the period 1998–2016, comparing MS incidence in three groups: users of systemic retinoids; users of topical retinoids (negative control group); and users of non‐retinoid acne drugs (control group). We used data from the Danish Multiple Sclerosis Registry (DMSR), the Danish National Prescription Registry and the Danish National Patient Registry. Linkage was obtained through the personal identification number (CPR number). We addressed confounding by three‐way propensity score (PS)‐matching weights. Additionally, to evaluate a cumulative dose–response effect for systemic retinoids on MS incidence, we conducted a case–control study, nested within the cohort. Results: A total of 257, 193 users of non‐retinoid acne drugs, 130, 560 users of topical retinoids, and 75, 610 users of systemic retinoids were included. Systemic retinoid use was not associated with a reduced risk of MS compared to non‐retinoid acne drug use in crude (hazard ratio [HR] 0.80, 95% confidence interval [CI] 0.61 to 1.05]) and weighted analyses (HR 0.89, 95% CI 0.67 to 1.20). There was no evidence of a cumulative dose–response association between systemic retinoids and MS incidence. Conclusions: Use of systemic retinoids was not associated with a reduced incidence of MS compared to use of non‐retinoid acne drugs in this study. Abstract : In this observational study, we explored the relationship between exposure to retinoids, mostly used in acne, albeit with diverse immunomodulatory effects, and multiple sclerosis (MS). We performed a nationwide cohort study in the Danish population comparing MS incidence in three groups: users of systemic retinoids; users of topical retinoids (negative control group); and users of non‐retinoid acne drugs (control group). Systemic retinoid use was not associated with a reduced risk of MS compared to non‐retinoid acne drugs; also, there was no evidence of a cumulative dose–response association between systemic retinoids and MS incidence.